"Go" signal intensity influences the sprint start - Brown, A. M.; Kenwell, Z. R.; Maraj, B. K. V.; Collins, D. F. (Medicine & Science in Sports & Exercise, 2008)
Introduction: Loud sounds can decrease reaction time (RT) and increase force generated during voluntary contractions. Accordingly, we hypothesized that the loud starter's pistol at the Olympic Games allows runners closer to the starter to react sooner and stronger than runners farther away.